ANALISIS PERBAIKAN POSTUR TUBUH SISWA SMP BHINNEKA TUNGGAL IKA DALAM MENINGKATKAN KENYAMANAN BELAJAR DENGAN METODE OVAKO WORK ANALYSIS SYSTEM (OWAS) - Subchan Asy’ari (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2020)
Posture of VIII grade students of SMP Bhinneka Tunggal Ika which has a big influence on the onset of musculoskeletal complaints is the position of the back and legs. In the back position there are often complaints felt by the students, namely in the musculoskeletal part because during teaching and learning activities (KBM) the back position of the students is bent. On the feet, it is seen that students learn with their legs bent / folded which results in frequent feeling of stiffness in that part. This study was conducted to determine the complaints of Musculoskeletal Disorders (MSDs) and the ergonomic risks that occur in students during the learning process. This study uses the Ovako Work Analysis System method to identify improvement activities that must be carried out. The results of this study indicate that the position of the body during KBM has a dangerous influence or effect on the musculoskeletal system. High risk in the position of the legs causes the risk of injury and sooner or later there will be a system disorder in the musculoskeletal system.